Valorization of Berries’ Agro-Industrial Waste in the Development of Biodegradable Pectin-Based Films for Fresh Salmon (Salmo salar) Shelf-Life Monitoring - Janira Romero; Rui M. S. Cruz; Alexandra Díez-Méndez; Irene Albertos (International Journal of Molecular Sciences, 2022)
The healthy properties of berries are known; however, red fruits are very perishable, generating large losses in production and marketing. Nonetheless, these wastes can be revalued and used. The main objective of this study was the development of biodegradable pectin films with berry agro-industrial waste extracts to monitor salmon shelf-life. The obtained extracts from blueberries, blackberries, and raspberries wastes were evaluated in terms of flavonols, phenols and anthocyanins contents, and antioxidant capacity. Then, pectin films with the extracts of different berries were developed and characterized. The results showed that the blueberry extract film was thicker (0.248 mm), darker (L* = 61.42), and opaquer (17.71%), while the highest density (1.477 g/cm3) was shown by the raspberry films. The results also showed that blueberries were the best for further application due to their composition in bioactive compounds, antioxidant capacity, and color change at different pHs. The salmon samples wrapped in blueberry films showed lower values of pH and deterioration of fish during storage compared to the control and pectin samples. This study contributes to the valorization of berries agro-industrial waste by the development of eco-friendly films that can be used in the future as intelligent food packaging materials contributing to the extension of food shelf-life as a sustainable packaging alternative.